Medial spike and obesity associate with open reduction in type III supracondylar humeral fracture - Çabuk, H; Dedeoğlu, S. S; Adaş, M; Tekin, A. Ç; Seyran, M; Ayanoğlu, S (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2016)
UNLABELLED: PURPOSE OF THE STUDY Although supracondylar humeral fractures represent a major part of the pediatric fractures, no classification system or radiological characteristics describes which supracondylar fractures require open reduction. We aim to evaluate the factors that lead us to perform open reduction during operation. MATERIAL AND METHODS We retrospectively evaluated 57 patients who underwent operation for type III supracondylar fracture, and divided them into two groups; those with open reduction and internal fixation, and those with closed reduction and percutaneous fixation. The two groups were compared based on age, gender, BMI by age, medial spike angle of the fracture, medial spike-skin distance and rotation angle between the fractured fragments. RESULTS Of all patients, 46 (81.71%) underwent closed reduction and percutaneous fixation (CRPF) and 11 (19.29%) were treated with open reduction and internal fixation (ORIF). BMI by age was remarkably higher in the ORIF group (p = 0.00). And medial spike angle was smaller in the ORIF group (p = 0.014). DISCUSSION Closed reduction and percutanous fixation is the main treatment of supracondylar humeral fractuers. Open reduction in supracondylar humeral fractures could be associate with complications and cosmetic lesions. Many studies indicates that obesity is high risk factor for complex fractures as well as preoperative and postoperative complications. A prominant medial spike could associate with muscle entrapment, and obliquity of the fracture line. It could be also an indirect finding of instablity of the fracture. CONCLUSION We suggest that a smaller medial spike angle and a higher BMI in children with Type III supracondylar humeral fractures may require open reduction, and it is unreasonable to avoid open reduction in cases where closed reduction is not achieved. KEY WORDS: supracondylar humerus, open reduction, obesity, medial spike angle.
Keywords: Open Fracture Reduction; předškolní dítě; retrospektivní studie; fixace fraktury; fraktury humeru; Child; otevřená repozice fraktury; vnitřní fixace fraktury; Humans; lidé; Retrospective Studies; Treatment Outcome; Fracture Fixation, Internal; kostní hřeby; Female; Male; Body Mass Index; výsledek terapie; uzavřená repozice fraktury; mužské pohlaví; ženské pohlaví; index tělesné hmotnosti; Closed Fracture Reduction; Postoperative Complications; Child, Preschool; Humeral Fractures; Bone Nails; pooperační komplikace; dítě; Fracture Fixation